Chemical processing of ceramics - Lee, Burtrand Insung; Pope, Edward J. A (Materials engineering (Marcel Dekker, Inc.), 1994)
a Details the chemical procedures used to characterize and synthesize ceramic materials, presenting specific examples of classes of ceramic materials fabricated by chemical processes. New ceramic processing technologies that can be used in ceramic membrane preparation are considered.